A Diachronic Maltese Islandscape: Rural Ta’ Qali and ix-Xarolla - Vella Clive (De Gruyter, 2021)
The archaeological study of the Maltese Islands has received considerable scholarly attention in regard to its island settings and long-term human occupation. However, emphasis on the prehistoric periods of the archipelago runs the risk of creating a biased focus with limited engagement in successive periods. In the spirit of this edited volume, the present article seeks to provide a broader chronological view of two rural areas in the larger island of Malta: Ta’ Qali and ix-Xarolla. These two areas have offered some evidence, through intermittent discoveries from recent construction activities, of three broad periods of increased landscape manipulation and transformation during the Middle-Late Bronze Age, Roman, and Early Modern periods. In seeking to provide an islandscape-based narrative, this article seeks to show that the Maltese Islands experienced periods of more intense human occupation that would have inevitably impacted the agriculturally viable areas of Ta’ Qali and ix-Xarolla. Therefore, despite the Roman period focus of this edited volume, this article takes a long-term view of two rural areas to illustrate identifiable landscape uses and changes.